Survey on the visualization technologies of threatening security data in cyber space - Fan ZHANG; Fan XIE; Jie JIANG (网络与信息安全学报)
With the rapid development of the cyber threatening methods,the requirements of network security data analysis become more and more imperative.Data visualization has already evolved as a requisite tool among all kinds of data analysis theory framework and applications,especially in the fields of scientific computation,business intelligence and cyber security.Threatening security data visualization provides various effective interaction means which improve the perception ability for the cyber security specialists to get a distinctive insight into the large amount of complicated cyber security problems.The state-of-art cyber security data visualization technologies were introduced.Some existing problems that were still challenging research topics were investigated.Some directions for future studies were outlined.